The Relationship of Motivation and Perceived Parental Encouragement with English Oral Skills Achievement of Grades 6 to 8 Students at Kpis International School, Bangkok - Contreras, Marie Anallie Santos; Lynch, Richard (Scholar: Human Sciences, 2018)
The purpose of this study was to determine the level of KPIS International School Grades 6-8 students’ motivation, perceived parental encouragement and achievement in learning English oral skills as well as their relationship with each other. A motivation questionnaire was used to collect data from 81 Grades 6-8 students studying Language Arts in the academic year 2016 - 2017 at KPIS International School. Means, standard deviations, multiple correlation coefficient and multiple linear regression were used to analyze the data. The findings showed that the respondents had a slightly high level of motivation, perceived parental encouragement and English oral skills achievement. Amongst the subscale of motivation, students were mostly motivated integratively, followed by instrumentally and were least motivated by their attitudes to the learning situation. The relationships among the variables were investigated and it was found that all three had significant positive relationships with each other. Between motivation and perceived parental encouragement, motivation had a stronger relationship and could explain a higher percentage of variance of English oral skills achievement.